Zero-Base Budgeting Comes of Age/Zero-Base Planning and Budgeting: Improved Cost Control and Resource Allocation. - Pattillo, James W. (The Accounting Review, 1978)
Abstract Reviews the books "Zero-Base Budgeting Comes of Age," by Logan M. Cheek and "Zero-Base Planning and Budgeting: Improved Cost Control and Resource Allocation," by Paul J. Stonich.